Romantic Relationships and Mental Health During the COVID-19 Pandemic in Austria: A Population-Based Cross-Sectional Survey - Till, Benedikt; Niederkrotenthaler, Thomas (Frontiers in Psychology, 2022)
Background Previous studies suggest that romantic relationships can be beneficial to mental health, but may also be a major stressor depending on specific relationship characteristics. Studies examining the role of romantic relationship in mental health are scarce. This study aimed to investigate differences in mental health with regards to relationship characteristics. Methods We assessed individuals’ mental health, i.e., suicidal ideation (via Beck Scale for Suicidal Ideation, BSS), depression (via Patient Health Questionnaire, PHQ-9), anxiety (Hospital Anxiety and Depression Scale, HADS), experience of psychological and physical violence, including changes in suicidal ideation and anxiety compared to before the pandemic, and relationship characteristics (i.e., relationship status, satisfaction, and commitment as well as family structure) with online questionnaires in a population-based cross-sectional study with 3,012 respondents in Austria during the COVID-19 pandemic. Results There were small to medium–sized group differences with regards to relationship status and satisfaction (ηp2: 0.011–0.056). Most mental health outcomes were less favorable in singles than in individuals in happy relationships, but scores for anxiety (p < 0.001), psychological (p < 0.001) and physical violence (p < 0.001), and the probability of experiencing an increase in anxiety compared to before the pandemic (p < 0.01) were lower in singles as compared to those with low relationship satisfaction. Furthermore, scores for suicidal ideation (p > 0.001) and psychological (p > 0.01) and physical violence (p > 0.01) were highest in individuals in relationships with low commitment and with a child living in the same household, but effect sizes were small (ηp2: 0.004–0.015). Conclusion During the COVID-19 pandemic, as compared to singles, mental health appeared worse in individuals with low relationship satisfaction and those in a relationship with low commitment and with a child in the household. Living in a happy relationship was associated with somewhat better mental health.